N10 Experience with telemedicine during the COVID-19 pandemic and preferences for future e-health in a large IBD cohort. (27th May 2021) - Breiteneicher, S; Le Thi, T G; Klucker, E; Schwerd, T; Csollarova, K; Neuhaus, L; Koletzko, S; Török, H; Koletzko, L
Abstract: Background: The COVID-19 pandemic affects clinical care, daily life and wellbeing of patients with IBD. During the contact restrictions, we realized anxiety among our IBD patients and unmet needs for healthcare. We investigated patient's experience with telemedicine (TM) during the pandemic, their interest in future TM use, and their preference regarding a qualified IBD Nurse-led or a Medical Doctor-led (MD-led) teleconsultation at a large German IBD center. Methods: Pediatric and adult patients who attended the IBD unit at least once between 7/2018 and 6/2020) were invited to a prospective survey (KoCo19-CED-1). Questions included items on IBD (phenotype, treatment and disease activity), comorbidities, healthcare utilization, demographic and socioeconomic factors, psychological burden and IBD-related quality of life during the COVID-19 pandemic. This sub-analysis presents patient's experience with TM and their preference for a contact with an IBD Nurse. Results: Of 820 identified IBD cases, 504 (62%) patients and/or their parents completed the survey between mid-July to mid-October 2020; 86 were children (aged 6 to 18 years) and 418 were adults (up to 85 years); 58.7% had Crohn's disease and 35.7% Ulcerative Colitis. Current treatment with any immunosuppressive medication (mono- or combo-therapy with immunomodulators, biologics, JAK-inhibitors and/or corticosteroids) were reported by 79.6% (401/504) of patients. During the pandemic, an in-person visit was substituted with TM by an IBD Nurse or a medical doctor (MD) in 58 (11.6%) and 29 (5.8%) of the patients, with high satisfaction (88.5% vs 92.1 %, respectively, n.s.). Half of the patients (n=246) showed interest in future TM, thereof 60.2% preferred consultation with a MD, 1, 6% with an IBD Nurse and 38.2% expressed no preference. Of patients with prior experience with an IBD Nurse-led TM (n=38), 96% are interested to use TM in the future. Rejection of future TM was related to no TM experience (p=0.001), having Crohn's disease (p=0.032), receiving biologics (p=0.004), and self- or non-employment status (p=0.003), but not to gender, age, self-reported disease activity or disease duration. Conclusion: Patient acceptance of TM is high, particular in those with previous TM experience, regardless of performed by MD or IBD Nurse. Our data support the statement on e-health in the N-ECCO 2018 Consensus giving an advanced IBD Nurse alongside with MD a key role to improve IBD care.